Western Kansas Field Station Weather Report: 2022 Growing Season - Dewayne Bond; Matthew Sittel (Kansas Agricultural Experiment Station Research Reports, 2023)
Summary of 2022 weather for research conducted at the research locations included in the 2023 Western Kansas Agricultural Research report.
Keywords: 2022 weather; western Kansas weather; Garden City; Hays; Tribune; Colby; Great Bend